Regional study of sea surface temperature, chlorophyll and aerosol concentration in the north atlantic ocean using modis data - Topham, Ricardo; Marcello, Javier; Eugenio, Francisco; Hernandez-Guerra, Alonso (2012)
Changes in environmental parameters such as sea surface temperature, chlorophyll concentration and aerosol optical depth, need to be considered since they are believed to be directly related to climate change. A detailed study has been conducted to obtain several maps highlighting those areas presenting a greater variation. This way, a regional evaluation can be performed and the relationship between the three parameters can be assessed. In this context, our work aims to analyse their impact in the North Atlantic Ocean (latitudes 15° to 45°N and longitudes 10° to 80°W). This area is one of the most sensitive to the effects climate change, so it is important to study the temporal and spatial changes of these parameters in order to predict their future variability. The remote sensing data used is provided by the MODIS sensor aboard NASA's Aqua and Terra satellites, and covers the period 2000-2011. Copyright © (2012) by the International Astronautical Federation. 3244 3239